MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION - HM Sujiyono Ps (Manajer Pendididikan, 2017)
The purpose of the study is to examine the results of implementation of the model type koorporatif team assisted individualization in the subject of islamic religious education.  Care bodies is one of the basic competencies that this evaluation includes aspects kognetif, affectif and psychomotor students is successful if it results in accordance with the indicator, appropriate learning models used models koorporatif  type team assisted individualization. This research is done with action research with two cycles, conclusions from this study that the teaching model type team assisted individualization is very appropriate in the treatment of material bodies and have a positive impact so as to improve student achievement.